AKUNTANSI TABUNGAN EMAS PEGADAIAN SYARIAH - Rosyida Iriani; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
Gold savings product is one of the first gold investment product that is available in Indonesia issued by Pawnshop, including Islamic Pawnshop and using a system of buyingsaving gold, and the agreement of gold svings product used is a contract of sale and purchase or akad murabahah. This research aims to find out the accounting treatment of gold savings, especially the aspects of recognition, measurement, disclosure, and presentation in Islamic Pawnshop This research uses qualitative method. Data collecting techniques used are interview and taking financial statement on official website of PT. Pegadaian. The result of this research shows that there is no difference between gold savingsin Islamic Pawnshop and conventional Pawnshop, including the accounting treatment, gold savings product uses accounting of gold sale and purchase and Gold inventory is recognized as Mulia gold inventory because inventory from gold savings is still incorporated with Mulia.  REFERENCESHidayat, Taufik. 2011. Buku Pintar InvestasiSyariah. Jakarta: Media KitaJuan, Ng Eng dan Ersa Tri Wahyuni. 2013. Panduan Praktis Standar Akuntansi Keuangan. Edisi Kedua. Jakarta: Salemba EmpatMoleong, Lexy J. 2001. Metode Penelitian Kualitatif. Bandung: PT. Remaja RosdakaryaQuthb, Sayyid. 2001. TafsirFi Zhilalil Qur’an : Dibawah Naungan Al-Qur’an (Surah Ali Imran- Annisa 70). Jakarta: Gema Insani Reeve, James M Dkk. 2013. Pengantar Akuntansi Adaptasi Indonesia. Jakarta: Salemba Empat Rudianto. 2012. Pengantar Akuntansi Konsep Dan Teknik Penyususnan Laporan Keuangan. Jakarta : Penerbit ErlanggaStandar Akuntansi Keuangan. 2012. Ikatan Akuntan IndonesiaSugeng, Anggoro. 2012. Analisis Prinsip Ekonomi Islam Terhadap Operasional Produk Investasi Emas Pada Perbankan Syariah X. Jurnal La-Riba, Volume VI No.2Sugiyono. 2010. Metode Penelitian Kuantitatif Kualitatif Dan R&D. Bandung : AlfabetaSuryomurti, Wiku. 2011. Supercerdas Investasi Syariah. Jakarta: QultumMediaWarren, Dkk. 2005. Pengantar Akuntansi Adaptasi Indonesia. Edisi 21. Jakarta: Salemba EmpatWiroso. 2011. Akuntansi Transaksi Syariah. Ikatan Akuntan Indonesiawww.pegadaian.co.id Yahya, Marzuqi. 2012. Jurus Cerdas Investasi Emas. Jakarta: Laskar Aksara